Solar-driven absorption cooling system with latent heat storage for extremely hot climates - Mehmood, S; Lizana, J; Friedrich, D (Elsevier, 2023)
Novel renewable cooling systems are required worldwide to address the growing demand for cooling. This study proposes and demonstrates a novel integration of solar-driven absorption cooling with latent heat storage to maximise the use of renewable energy for cooling in extremely hot climates. A parametric analysis was performed in TRNSYS to identify the critical parameters for optimal sizing related to the solar field size, tank volume, tank insulation, auxiliary heating set point, and collector tilt angle. Moreover, the integration was compared with a conventional solar-driven absorption cooling system using sensible heat storage (a hot water tank) and an electric-driven vapour compression cooling system. The results show that a solar field size of 1.5 m2/kWc, a latent heat storage tank volume of 30 L/m2, adequate insulation below 0.8 W/m2.K, and appropriate set-point temperatures for the auxiliary boiler provide the optimal performance to maximise the solar fraction. Compared with conventional solar-driven absorption cooling, the study demonstrates how the phase change material (PCM) increased the solar fraction by 4.2 % (from 70.3 to 74.5 %) due to higher stable temperature and lower tank losses (reduced by 44 %). In addition, despite the higher initial investment cost of the proposed PCM-based solar-driven cooling system compared to the vapour compression cooling system, the findings highlight that the life cycle cost is much lower in extremely hot climates. After 25 years, the life cycle cost was lowered by 34 % compared to vapour compression and by 9 % compared to a conventional solar-driven cooling system. Compared to vapour compression refrigerant technology, the proposed system can save 31.6 % of primary energy and 1222 kgCO2eq annually. This research provides valuable insights into the optimal design and integration of renewable cooling for residential applications in extremely hot regions.